EVALUASI PROSES PENYELENGGARAAN PILKADA LANGSUNG (Studi Kasus di Kalimantan Timur) - Said Fadhil (Jurnal Borneo Administrator, 2007)
Implementation of free and open election represents one of the prerequisites of a governance, which is categorized as democratic governance. Since 2005 more than 50% of the total area in Indonesia have carried out direct election of district head. However, various problems still emerge. Money politic issue, conflict between supporter, collision of campaign regulation up to the close opportunity for civil candidate (independent) are some problems which are still faced in the implementation of direct election. This article tries to identify and analyze the stages of direct election implementation as well as to compare the practice and problems which emerge in the execution, especially in East Kalimantan. In fact, from result of the analysis, there are still many weakness and insufficiency either both from the aspect of regulation or in the execution of direct election which must be straighten up, either from the aspects of law, implementation instrument or technical during the execution  Keywords: Direct Election of District Head, Local Democracy.